Gestión administrativa en el ferricentro del cantón baba. - Pin Anchundia, Joe Nicolás (2022)
Given the disadvantage of the economic growth of the Ferricentro of the canton Baba, it is considered that this is caused by poor administrative management and inadequate participation in the work area by each of the collaborators within the organization, and also by the lack of control by the owner of the same. Considering these points as situations for which there are dissatisfied consumers due to the lack of attention in the company towards them. In order to evaluate the degree of efficiency and effectiveness in the use of the functions of business management within the organization we rely on the techniques and administrative processes that allow us to achieve a pre-established objective, giving a better order on it. Within this case study, we delved into the subject of administrative management, since the objective is to visualize the factors that threaten the hardware store, thus trying to collect as much information as possible to detect each of the errors that lead to a great risk to the liquidity of the company and thus to consider the importance of business management strategies. We can emphasize that the administration allows the correct development of any activity through its processes: planning, organizing, directing and organizing. It is to affirm that the investigation of each one of the topics of this work is supported with investigations of professionals in the field of business management, administration, scientific articles, magazines and books.